An Inexpensive Route to Synthesize High-Purity CrO2 for EMI Shielding in X-Band Frequencies. (19th March 2012) - Verma Verma, Vivek Vivek; Ahmad Ahmad, Shahab Shahab; Dar Dar, Abdullah Abdullah; Kotnala Kotnala, R. R.
Abstract : Rod-shaped high-purity samples of CrO2 have been synthesized by an inexpensive and simplified procedure. Here, we have prepared pure CrO2 without applying any external pressure or control it during synthesis. The sample prepared exhibited an improvement in saturation magnetization values, 68 emu/g at 300 K, 136 emu/g at 80 K, and uniform grained microstructure. The complex permittivity, permeability, and microwave absorption properties of high-purity CrO2 sample were investigated in the 8.2–12.2 GHz (X-band) microwave frequency range. Microwave measurements have shown the high shielding effectiveness due to absorption (SEA ) of 20.3 dB. The high value of SEA suggests that CrO2 can be used as a promising electromagnetic shielding, EMI, material in 8.2–12.2 GHz (X-band) microwave frequency range.